Empowering Indigenous Communities through Cultural Festivals: An Islamic Economic Perspective on Income-Generating Projects in Jayapura, Papua - Syarifudin, Moh.; Imam Wayudhi (El-Qist: Journal of Islamic Economics and Business (JIEB), 2025)
This study aims to explore the economic empowerment potential of cultural festivals in indigenous communities through an Islamic economic lens, using the Lake Sentani Festival in Jayapura, Papua, as a case study. Employing a qualitative descriptive method, the research gathers empirical data from indigenous micro-entrepreneurs, local officials, and festival organizers via interviews, field observations, and document analysis. The findings reveal that Income-Generating Projects (IGPs) embedded within cultural festivals can significantly enhance local economic activity, particularly when grounded in sharia principles such as distributive justice (‘adl), public benefit (maṣlaḥah), and mutual cooperation (ta‘āwun). However, only 20% of the indigenous population is directly involved in festival-related economic activities, indicating structural exclusion and limited access to institutional support. Moreover, 90% of commercial activities remain confined to traditional product sales, highlighting a critical need for diversification and innovation. This study contributes to the global discourse on Islamic community-based development by proposing a four-pillar sharia-based model—shura-driven governance, maqāṣid-oriented policies, ethical multi-stakeholder collaboration, and integrated MSME development. It offers actionable insights for policymakers to transform cultural events into inclusive, sustainable platforms that merge cultural preservation with ethical economic empowerment. The model has broader applicability for Muslim communities worldwide seeking to align local heritage initiatives with Islamic economic principles.This study aims to investigate the role and potential impact of Income-Generating Projects (IGPs) embedded within cultural festival activities in Jayapura Regency as a strategic approach to local economic empowerment. While cultural festivals are widely recognized for preserving heritage and attracting tourism, they often struggle to deliver equitable economic gains to indigenous communities. Employing a qualitative descriptive methodology, the study gathers empirical data through interviews, field observations, and document analysis. The Lake Sentani Festival serves as the focal case, with participants including local residents, MSME operators, and regional government officials. The findings indicate that IGPs—particularly those involving the sale of indigenous products and the organization of local markets—can significantly increase community income when coupled with inclusive participation. This research contributes to the emerging field of community-based cultural economics by positioning cultural festivals as catalysts for grassroots empowerment. Framed through the lens of Islamic economics, the study introduces a development model rooted in foundational sharia principles such as distributive justice (al-ʿadl), public interest (maṣlaḥah), and mutual cooperation (taʿāwun). Cultural festivals are thus conceptualized as strategic vehicles for enhancing microenterprise engagement, expanding access to economic resources, and fostering entrepreneurship aligned with Islamic ethical values. By integrating local cultural assets with participatory Islamic economic frameworks, this study offers a novel contribution to inclusive and sustainable development, particularly in socially and economically marginalized regions such as Papua.